2016
DOI: 10.1007/s00484-015-1131-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heat tolerance and production performance of Aardi, Damascus, and their crossbred goats

Abstract: The question of whether the adaptability and production performance in goats may be enhanced using a crossbreeding program between bucks of a native and heat-tolerant breed and does of an exotic and dual-purpose breed was approached and examined herein by comparing purebred Aardi and Damascus goats and their crossbred lines (i.e., (1)/2 Aardi (1)/2 Damascus (½A½D) and (1)/4 Aardi (3)/4 Damascus (¼A¾D)) reared in a region characterized by dry and hot bioclimatic conditions. Twenty-four male 6-month-old kids ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Reducing the level of water intake under such conditions had no subsequent impacts on the thermal status of lambs fed on PCD based on the un-altered findings of their body temperatures and thermal gradients (Table 1, Figure 2). Exposure to hot weather conditions could trigger an increase in T r , T sk , heart rate, as well as other thermo-physiological indices (Abdoun et al, 2012;Al-Haidary et al, 2012;Samara et al, 2016), however, this was not the case herein since lambs were reared under thermo-neutral condition. In fact, Alamer (2010) observed no change in T r of waterdeprived Awassi and Najdi sheep during the winter season.…”
Section: Discussionmentioning
confidence: 87%
“…Reducing the level of water intake under such conditions had no subsequent impacts on the thermal status of lambs fed on PCD based on the un-altered findings of their body temperatures and thermal gradients (Table 1, Figure 2). Exposure to hot weather conditions could trigger an increase in T r , T sk , heart rate, as well as other thermo-physiological indices (Abdoun et al, 2012;Al-Haidary et al, 2012;Samara et al, 2016), however, this was not the case herein since lambs were reared under thermo-neutral condition. In fact, Alamer (2010) observed no change in T r of waterdeprived Awassi and Najdi sheep during the winter season.…”
Section: Discussionmentioning
confidence: 87%
“…Simple shelter with straw or hay or aluminum sheets as the rooftop can be very effective for even semi-intensive rearing practices. Provision of shade to the sheep and goats was found to improve body weight gain, milk production, and reproductive performance [77]. Installation of fans or other cooling systems in the sheds can minimize heat stress [77].…”
Section: Alleviation Strategies For Heat Stressmentioning
confidence: 99%
“…Provision of shade to the sheep and goats was found to improve body weight gain, milk production, and reproductive performance [77]. Installation of fans or other cooling systems in the sheds can minimize heat stress [77]. Because the water requirements of sheep and goats increase under heat stress conditions, access to adequate cool freshwater, therefore, is one of the best practices to reduce heat stress [74,77].…”
Section: Alleviation Strategies For Heat Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation will lead to more uncertainty for food, occupational options for the rural population, farm yield and grazing system ("AR5 Climate Change 2014," n.d.; Ndiritu, 2020). Earlier studies suggested that the small ruminants can tolerate and thrive in the harsh environment of the arid and semi-arid zone (Samara et al, 2016). Sheep rearing is a common occupation for the people residing in the arid and semi-semi-arid region and it serves as vital economic activity (Gowane et al, 2020) for the small and marginal farmers.…”
Section: Introductionmentioning
confidence: 99%